Effect of phytohormones and genotype on meristem and shoot tip culture of teifaira occidentalis hook F (2012)
Objectives: The aim of this work was to investigate the effect of plant growth regulators (PGR), genotype and explant type on in vitro shoot induction, elongation, and multiplication in Telfairia occidentalis. Methodology and Results: In this study attempts were made to induce shoots from meristem and shoot tip culture of Telfairia occidentalis Hook F. Shoot apical meristems with 1-2 leaf primordia and shoot tip explants were aseptically isolated and cultured on ½ N6 medium supplemented with different combinations of 2mg/l BAP, IAA and kinetin. Explants were derived from seedlings of two T. occidentalis genotypes grown in sterilized soils inside vials in the laboratory. Regeneration response were examined based on five parameters – callus formation, shoot length, number of shoots per explant, number of leaves per explant and number of nodes. Shoot induction, elongation and multiplication were most effectively promoted by the medium supplemented with 2.0 mg/lBAP + 2.0 mg/l IAA for shoot tip culture, while 2.0 mg/l BAP was most effective for shoot regeneration from meristem culture. Genotype I was significantly higher than Genotype II in shoot bud regeneration response (p<0.05). Culture of explants from shoot tip led to better shoot egeneration in comparison to explants from meristem. Callus formation/induction was also influenced by explants and media interaction. Conclusion and Application of Findings: In vitro shoot induction from meristem and shoot tip culture of T. occidentalis has been demonstrated. These in vitro culture procedures would be useful for developing uniform clones or micropropagation and could also form the basis for in vitro storage of explants and subsequent regeneration of plantlets after long term conservation in this species. The recalcitrant nature its seeds makes alternative means of genetic resources conservation very necessary. More importantly, meristem culture technique is useful for developing virus-free clones and avoids the limitations imposed by conventional mode of planting. Calli produced could also be excellent targets for genetic transformation and improvement of this species.